2017
DOI: 10.5114/reum.2017.71638
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of histopathological examinations of non-renal biopsies in the diagnosis of granulomatosis with polyangiitis

Abstract: IntroductionGranulomatosis with polyangiitis (GPA) is a rare, ANCA-associated, systemic disease characterized by necrotizing small and medium vessel vasculitis of unknown etiology associated with granulomatous inflammation affecting the renal, pulmonary, upper airways, ocular systems and other tissues. Histological proof of the granulomatosis with polyangiitis (GPA) can be obtained by biopsy of clinically involved sites. The main purpose of this study was to examine histopathological changes in non-renal biops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 22 publications
(30 reference statements)
2
19
0
1
Order By: Relevance
“…The gold standard for diagnosing childhood vasculitis is with either histopathology from tissue biopsy or by characteristic lesions detected by imaging studies. Multiple studies in adults with AAV have found that less than half of all biopsies show the characteristic inflammatory and vasculitic changes to confirm the diagnosis [ 15 17 ], and sampling difficulty is often a limitation which could have explained our patient’s biopsy findings. Different classification criteria have been proposed to diagnose GPA in children [ 5 , 18 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The gold standard for diagnosing childhood vasculitis is with either histopathology from tissue biopsy or by characteristic lesions detected by imaging studies. Multiple studies in adults with AAV have found that less than half of all biopsies show the characteristic inflammatory and vasculitic changes to confirm the diagnosis [ 15 17 ], and sampling difficulty is often a limitation which could have explained our patient’s biopsy findings. Different classification criteria have been proposed to diagnose GPA in children [ 5 , 18 20 ].…”
Section: Discussionmentioning
confidence: 99%
“… 1 Pulmonary biopsy has a sensitivity ranging from 10 to 80% while the sensitivity of biopsies from the nose or sinuses is estimated at 20–50%. 5 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, a biopsy of extra renal tissue has a rather low yield for a definitive diagnosis of ANCA-related vasculitis, and in many cases, it is necessary to repeat biopsy and make repeated attempts to establish the diagnosis. 10…”
Section: Discussionmentioning
confidence: 99%